Tungsten-based sintered alloy, manufacturing method thereof, and discharge electrode member and spark plug using the same

By adjusting the Ni, Fe and Cu content in the W-based sintered alloy, controlling the linear density and standard deviation of their grain boundary phases, the problem of large density and hardness variability is solved, the processability and size maintenance ability are improved, and more efficient product processing and better quality are achieved.

JP7664794B2Active Publication Date: 2025-04-18NITERRA MATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021139667
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-30
Publication Date
2025-04-18
Estimated Expiration
2041-08-30

AI Technical Summary

Technical Problem

During the miniaturization process, the existing W-based sintered alloy has a high variability in density and hardness, resulting in increased difficulty in cold plastic processing and poor size maintenance, which affects the production efficiency and quality of the product.

Method used

By adjusting the content range of Ni, Fe and Cu, it is ensured that the grain boundary phase of W-based sintered alloy is mainly composed of Ni, Fe and Cu, and the grain boundary phase density is controlled between 0.05 and 0.50 and the standard deviation is between 0.05 and 0.10 in the sectional area of ​​270μm x 270μm.

Benefits of technology

The variability of density and hardness of W-based sintered alloy is improved, its processability and size maintenance capabilities in cold plastic processing, and its production efficiency and quality are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007664794000003
    Figure 0007664794000003
  • Figure 0007664794000004
    Figure 0007664794000004
  • Figure 0007664794000005
    Figure 0007664794000005
Patent Text Reader

Abstract

To provide a W group sintered alloy which improves variations in density and hardness of a sintered body of a W sintered alloy containing Ni, Cu and Fe in W, and has good workability, and a manufacturing method.SOLUTION: A W group sintered alloy contains 50 wt.% or more of W, and the balance Ni, Fe and Cu, where the structure of the W group sintered alloy has a grain boundary phase containing Ni, Fe and Cu as main components and W particles, and in a square region of 270 μm×270 μm in an arbitrary cross section of the W group sintered alloy, a ratio (linear density) of a length occupied by the grain boundary phase on a straight line orthogonal to an opposing side is 0.05 or more and 0.50 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] An embodiment of the present invention relates to a tungsten-based sintered alloy, a manufacturing method thereof, and a discharge electrode member and an ignition plug using the same. [Background technology]

[0002] Tungsten (W)-based sintered alloys have excellent oxidation resistance, low thermal expansion, high thermal conductivity, and mechanical properties at high temperatures, and are used in die-casting die parts, glass lens molded parts, semiconductor parts, and various electrodes. For example, the center electrode mounted on the spark plug of a gasoline engine is the anode part (discharge electrode part) that generates sparks at the time of ignition, and is exposed to the harshest environments. For this reason, the applicable material must be heat-resistant and corrosion-resistant, and W-based sintered alloys are used.

[0003] W sintered alloys, which contain nickel (Ni), copper (Cu) and iron (Fe), have excellent workability. In addition, they can produce dense sintered bodies at sintering temperatures 500°C lower than other W alloys. Due to these characteristics, W sintered alloys containing Ni, Cu and Fe are used for center electrodes.

[0004] The W sintered alloy used for the center electrode is made into a rod-shaped material with a diameter of 3 to 5 mm and a length of 10 to 13 mm by powder metallurgy, in which powder is molded and sintered. It is then processed as required to become the center electrode. If the metal structure of such a small sintered alloy varies after sintering, the resulting variations in density and hardness of the sintered body make it difficult to perform the required processing, such as cold plastic processing, required to make the center electrode. Or, the dimensions after processing vary greatly, making it impossible to meet the required dimensional tolerances, significantly reducing the product yield. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 5847196 [Patent Document 2] Japanese Patent Application Publication No. 6-279909 [Patent Document 3] JP 2004-353006 A Summary of the Invention [Problem to be solved by the invention]

[0006] The problem to be solved by the present invention is to provide a W-based sintered alloy containing W, Ni, Cu, and Fe, which has good workability and has improved variations in density and hardness of the sintered body, and a manufacturing method thereof. [Means for solving the problem]

[0007] In order to solve the above problems, the W-based sintered alloy according to the embodiment is Ni is 1.0wt% or more and 20wt% or less, Fe is 0.1wt% or more and 10wt% or less, Cu is 0.1wt% or more and 10wt% or less, The remainder Consists of tungsten and inevitable impurities In the W-based sintered alloy, the structure of the W-based sintered alloy has a grain boundary phase mainly composed of Ni, Fe, and Cu and W particles, and in a 270 μm × 270 μm square region in any cut surface of the W-based sintered alloy, the proportion of the length occupied by the grain boundary phase on a straight line crossing opposite sides at right angles (linear density) is 0.05 or more and 0.50 or less. The standard deviation of the linear density is greater than or equal to 0.05 and less than or equal to 0.10. [Brief description of the drawings]

[0008] [Figure 1] Example of cross-sectional structure of W sintered alloy according to embodiment [Diagram 2] Examples of W particle shapes and axes [Diagram 3] Schematic diagram showing an example of granulation using the spray drying method [Figure 4] Schematic diagram showing examples of the shape of granulated powder [Diagram 5] Schematic diagram showing an example of a spark plug DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, the W-based sintered alloy of the embodiment will be described with reference to the drawings. Note that the drawings are schematic, and for example, the dimensional ratios of each part are not limited to those shown in the drawings.

[0010] FIG. 1 shows an example of a cross-sectional structure of a W sintered alloy according to an embodiment. In FIG. 1, 1 is a tungsten-based sintered alloy, 2 is a tungsten particle, and 3 is a grain boundary phase. The tungsten-based sintered alloy 1 is sometimes called a W-based sintered alloy 1. The tungsten particle 2 is sometimes called a W particle 2. The cross-sectional structure is measured in a longitudinal cross section for ease of sample processing. The obtained cross section is polished and observed with a scanning electron microscope (SEM). The observation surface is, for example, a polished surface with a surface roughness Ra of 1 μm or less. In addition, by using a backscattered electron image in the SEM image, the W particle 2 and the grain boundary phase can be distinguished. There is a difference in contrast between the W particle 2 and the grain boundary phase, and the W particle 2 appears gray and the grain boundary phase appears black, so that the W particle 2 and the grain boundary phase can be distinguished. A square area of ​​270 μm×270 μm is set using an SEM image observed at 1000 times. With this field of view, the W particle 2 and the grain boundary phase can be clearly distinguished. In addition, many W particles 2 and grain boundary phases can be observed, making it suitable for measuring linear density. The grain boundary phase is a phase whose main components are Ni, Fe, and Cu, and here "main components" means that the total of each of the above elements is 80wt% or more. In a square area of ​​270μm×270μm, a straight line (L1) is drawn crossing the opposing sides at a right angle, and the length (A1 to A6) of the straight line crossing the grain boundary phase is measured. The linear density is calculated by the following formula: Linear density = "Sum of lengths crossing grain boundary phases (μm)" / 270 (μm). Two fields of view are observed per cross section of a sample, and five measurements are taken per field of view. Therefore, ten measurements are taken per sample. This measurement field of view and number of measurements are examples, but this method is good for measuring the entire W sintered alloy without bias. Sintering pores (P) are voids (pores). P is formed in W particles 2 or in the grain boundary phase. P is included in the grain boundary phase.

[0011] The linear density of the grain boundary phase in the embodiment is preferably 0.05 to 0.50, more preferably 0.10 to 0.50. In the W-based sintered alloy according to the embodiment, the linear density of any grain boundary phase measured is within the range of 0.05 to 0.50. If the linear density exceeds 0.50, the proportion of the grain boundary phase is high, so the hardness of the sintered body is low. In addition, the hardness variation is also large. If the hardness is low and the hardness variation is large, the processing dimensions during cold plastic processing are likely to vary. On the other hand, if the linear density is below 0.05, the hardness is high because the proportion of W particles is high. If the hardness is too high, cold plastic processing is difficult. In addition, the proportion of W particles in contact with each other increases. The grain boundaries between W particles are easily cracked during cold plastic processing.

[0012] The standard deviation of the linear density of the grain boundary phase in the embodiment is 0.10 or less. If the standard deviation exceeds 0.10, the workability of the sintered body varies, and the working dimensions during cold plastic working tend to vary. The lower limit of the standard deviation is not particularly limited, but is 0.05 or more, taking into account the variation of the manufacturing conditions. The standard deviation is determined from data on the linear density of the grain boundary phase obtained 10 or more times.

[0013] The shape and grain size of the W particles 2 are measured for a square region of 270 μm × 270 μm in the SEM image observed at 1000x magnification. All W particles 2 completely contained within the observation field are the subject of the measurement. Figure 2 shows an example of a method for measuring the shape and grain size of the W particles. The shape is determined by visually inspecting the image. The crystal grain size of the W particles is determined by measuring the orthogonal major axis (X) and minor axis (Y) of the W particle, and the average value = (Y + X) / 2.

[0014] The shape of the W particles in the SEM image observed at 1000x magnification is composed of boundaries that have no acute angles on the periphery. If the W particles after sintering have boundaries with acute angles, the sintering is often insufficient, which makes cold plastic processing difficult. In addition, the acute boundaries are likely to concentrate stress, which may lead to cracks during processing.

[0015] The average crystal grain size of the W particles in the embodiment is 20 μm or more and 40 μm or less. If the average crystal grain size is less than 20 μm, the grain boundary area of ​​the W particles is large, so the thickness of the grain boundary phase is small. Therefore, the ratio of W particles is large, and the hardness is high. If the hardness is too high, cold plastic processing is difficult. In addition, sintering is often insufficient, and as a result, cold plastic processing is difficult. If the average crystal grain size exceeds 40 μm, the grain boundary area of ​​the W particles is small, so the thickness of the grain boundary phase is large. Therefore, the ratio of the grain boundary phase is large, and the average hardness of the sintered body is low. In addition, the hardness also varies widely. If the hardness is low and the hardness variation is large, the processing dimensions during cold plastic processing are likely to vary.

[0016] The Vickers hardness (Hv) is measured using the sample that has undergone the above-mentioned structural observation. A load of 1 kgf is maintained for 10 seconds, and the indentation is observed and measured at 400x magnification. The measurement positions are random, and measurements are taken at least 10 times. It is confirmed whether the measured values ​​are within the specified range, and the standard deviation is calculated.

[0017] The hardness of the embodiment is 250Hv or more and 350Hv or less, and the standard deviation is 20Hv or less. Parts with a hardness exceeding 350Hv may cause cracks or breakage of the processing jig during cold plastic processing. Parts with a hardness less than 250Hv may not be sintered sufficiently, and may have internal voids or grain boundary phase segregation. In addition, if the standard deviation exceeds 20Hv, the processing dimensions during cold plastic processing are likely to vary. The lower limit of the standard deviation is not particularly limited, but is 10Hv or more in consideration of fluctuations in manufacturing conditions.

[0018] The composition of the W-based sintered alloy of the embodiment is Ni 1.0wt% to 20wt%, Fe 0.1wt% to 10wt%, Cu 0.1wt% to 10wt%, and the remainder is tungsten and inevitable impurities. The inevitable impurities refer to oxygen and carbon, and are contained in an amount of about 1 to 200wtppm. The contents of Ni, Fe, and Cu are analyzed by ICP emission spectroscopy, and oxygen and carbon are analyzed by infrared absorption.

[0019] The Ni component provides a liquid phase necessary for sintering the W powder and improves the grain boundary diffusion coefficient of W. If the Ni component is less than 1 wt%, the W-based sintered alloy does not become dense during sintering, and not only does it fail to obtain the desired specific gravity, but the strength also decreases due to the presence of residual voids. If the Ni component exceeds 20 wt%, the increase in the Ni liquid phase during sintering causes relative positional displacement of each W particle, resulting in deformation of the shape after cooling. In addition, the W content becomes relatively low, and the characteristics of the W base are impaired.

[0020] The Fe component can improve the strength of the binder phase by dissolving in the Ni component. If the Fe component is less than 0.1 wt%, no strength improvement effect is observed. If the Fe component is more than 10 wt%, the ductility is reduced and the W content is relatively low, which impairs the characteristics of the W base.

[0021] The Cu component generates a liquid phase at a lower temperature than Ni, improving sinterability. It also forms a bonding phase in the Ni-Fe-Cu composition, improving strength. If Cu is less than 0.1 wt%, the effect of improving sinterability is hardly observed, and improvement in strength cannot be ensured. If Cu exceeds 10 wt%, the W content becomes relatively low, and the characteristics of the W base are impaired.

[0022] Next, a method for producing the W-based sintered alloy according to the present embodiment will be described. The production method is not particularly limited, but the following method can be mentioned, for example.

[0023] (1) Raw material blending process Metal powders of W, Ni, Fe, and Cu are weighed and mixed. For example, the mixture is put into a ceramic pot container together with ceramic balls and mixed using a pot mill or the like. After mixing, if necessary, an analytical sample is taken and the components are analyzed by the above-mentioned method. It is also effective to grasp the mixing ratio of each component and the amount of unavoidable impurities.

[0024] (2) Granulation process It is preferable to granulate the powder to obtain good fluidity so that the powder can be uniformly filled in the molding die. To perform the granulation process, it is preferable to add a binder aqueous solution. The binder refers to an organic material such as polyvinyl alcohol (PVA), and a solid binder is dissolved in water or an organic solvent and used as a binder solution for granulation. From the viewpoint of equipment safety, it is preferable to use a binder aqueous solution using water. Figure 4 shows a schematic diagram of the shape of the granulated powder. Figure 4 (A) shows an example of granulated powder produced by the rolling granulation method. There are cases where granulated powder has a structure in which an agglomerated part (Ba) of the binder aqueous solution occurs inside the granulated powder and is surrounded by metal powder. The size of the agglomerated part (Ba) refers to a size of at least twice the average particle size of the raw metal powder or at least 100 μm. The size of the agglomerated part (Ba) refers to the longest diagonal line when observing any cross section of the granulated powder. The binder aqueous solution is removed at a low temperature during debinding and early sintering, but if a site such as Ba exists, a cavity will be formed after removal. During sintering, the added elements Ni, Cu, and Fe become liquid phase once and flow into the cavity. As a result, a large grain boundary phase region is generated in the sintered body. For this reason, the linear density of the grain boundary phase varies greatly. FIG. 4(B) shows an example of the granulated powder used in this embodiment. By mixing the mixed powder and the binder aqueous solution to form a slurry and granulating under the conditions described below, a granulated powder is obtained in which no site such as Ba exists and the metal powder and the binder aqueous solution are uniformly mixed. Since the binder aqueous solution exists uniformly, it remains uniform even after the binder aqueous solution is removed, and a sintered body with a uniform grain boundary phase can be obtained.

[0025] The mixed powder and the PVA aqueous solution are thoroughly mixed to produce a slurry. The binder aqueous solution is preferably a PVA aqueous solution. Mixing is performed using, for example, a ball mill. The balls to be put into the ball mill are preferably made of alumina, zirconia, or tungsten carbide. If there is a concern about the mixing of materials, mixing may be performed without using balls.

[0026] The PVA concentration after granulation is preferably adjusted to 1.0wt% or more and 2.0wt% or less with respect to the granulated powder. If the PVA concentration is lower than 1wt%, the resistance increases when the molded body is removed from the mold during molding, which may damage the mold. If the PVA concentration exceeds 2wt%, the amount of PVA that enters between the powder particles increases, making it easier for PVA aggregates to occur in the granulated powder, making it difficult to obtain homogeneous granulated powder and causing fluctuations in the linear density of the grain boundary phase. The PVA concentration is calculated as a percentage by measuring the weight of the molded body before and after the binder removal process described below and dividing the difference in weight of the molded body before and after the process by the weight of the molded body before the process.

[0027] The slurry concentration used for granulation is preferably 0.2 L / kg or more and 0.4 L / kg or less. The slurry concentration refers to the amount of PVA aqueous solution per 1 kg of raw metal powder. If the slurry concentration is less than 0.2 L / kg, the PVA concentration after granulation is likely to be lower than 1 wt%. In addition, the viscosity of the slurry increases, and the supply of the slurry during granulation becomes unstable and may become difficult. If the slurry concentration exceeds 0.4 L / kg, the amount of binder present in the gaps between the metal powder increases, and the PVA concentration after granulation is likely to exceed 2 wt%. In addition, during granulation by the spray drying method, uneven distribution of the metal powder may occur, and voids may occur in the granulated powder.

[0028] Next, the slurry is spray-dried to obtain granulated powder with good fluidity. Figure 3 shows a schematic diagram of granulation by spray drying. The slurry is fed into a dryer heated to 100-300°C with hot air. If the temperature is less than 100°C, the evaporation rate of the organic solvent is slow, so it takes a long time to dry. Or the drying is insufficient. If the temperature exceeds 300°C, it causes the particle size of the granulated powder to vary. The slurry is sprayed into the machine from a rotating disk part (atomizer). The rotation speed of the atomizer is preferably 8000 rpm or more and 14000 rpm or less. If the rotation speed is less than 8000 rpm, the variation in the size of the granulated powder increases, and large sizes are generated. There is a high possibility that the PVA concentration of this large granulated powder will exceed 2 wt%. If the rotation speed exceeds 14000 rpm, the metal powder and the binder will separate and be unevenly distributed due to the weight difference between them, and granulated powder as shown in Figure 4 (A) may be produced. In addition, small-sized granulated powder is easily produced, and the PVA concentration of these small-sized granulated powders is likely to be lower than 1 wt%. The obtained granulated powder may be passed through a sieve of a specified size. It is possible to remove excessively large granulated powder and excessively small granulated powder, and further to control the average particle size.

[0029] The fluidity of granulated powder is preferably 10 seconds / 50g or less. If it is greater than this, the powder will not be sufficiently packed into the mold during molding, and the molded weight will be insufficient for the designed value. Fluidity is measured by measuring the time it takes for 50g of powder to pass through a funnel with an inclination angle of 60 degrees and a hole diameter of Φ5mm.

[0030] The bulk density of the granulated powder (JIS-Z8890 5303) is 2.5g / cm 3 Above this is preferable. If it is smaller than this, the depth (height) of the molding die to fill the specified weight will be large. For this reason, molding may not be possible with existing equipment. Bulk density is measured in accordance with the Tungsten and Molybdenum Industry Association standard (TMIAS-0101 Powder Property Test Method).

[0031] (3) Molding (molding) process The granulated powder is filled into a mold and molded by pressing. The pressure is preferably 90 MPa to 300 MPa. If it is lower than 90 MPa, the molded body is likely to crack, and if it exceeds 300 MPa, the mold may be damaged when the molded body is removed.

[0032] (4) Debinding process The molded body is placed in a furnace at a temperature of 600 to 1000°C in a reducing atmosphere, and the PVA component used during granulation is removed.

[0033] (5) Sintering After the binder is removed, the molded body is sintered in a reducing atmosphere at a temperature between 1300°C and 1500°C. If the sintering temperature is lower than 1300°C, the normal metal structure will not be obtained due to insufficient sintering, and the density will not increase. If the temperature is higher than 1500°C, the sintering may proceed too much, causing the crystals to become coarse. Alternatively, internal voids may grow, resulting in coarse voids. A continuous furnace, batch furnace, etc. can be used as the sintering furnace.

[0034] The sintered density of the W-based alloy of the embodiment is 95% or more of the theoretical density. If it is less than 95%, the proportion of internal voids in the sintered body is high, which may cause cracks during cold plastic processing or cause discharge failure when used as an electrode. The sintered density is calculated by the underwater method, which measures the dry weight and underwater weight of the sintered body, and is calculated using the following formula. The apparent density is calculated using the following formula. Density = [dry weight / (dry weight - weight in water)] x density of water

[0035] Depending on the product shape, the molding process and the sintering process may be performed simultaneously using hot pressing (HP) or hot isostatic pressing (HIP). In that case, the atmosphere may be an inert gas such as nitrogen gas or argon gas.

[0036] The W-based sintered alloy produced in the above process is subjected to necessary processes such as vacuum heat treatment and machining under known conditions to produce a discharge electrode member or an ignition plug using the same. FIG. 5 is a schematic diagram showing an example of an ignition plug. The W-based sintered alloy is obtained after the above-described sintering process. The W-based sintered alloy is processed into a predetermined shape and dimensions to produce a discharge electrode member. A part composed of each part including the discharge electrode member is called an ignition plug. (Example)

[0037] The mixed powder obtained in the raw material blending process was granulated under different granulation conditions. Table 1 shows the powder composition and granulation conditions. The analysis was carried out by the method described above. In addition, in the rolling granulation of Comparative Example 5, the metal powder filled in the device was stirred at 70 to 100 rpm, the PVA aqueous solution was separately supplied, and the powder was granulated while hot air of 100 to 300°C was applied. The powder and the PVA aqueous solution were independent, and no atomizer was used, so the same condition evaluation could not be performed. This is indicated in the table by "-".

[0038] [Table 1]

[0039] The granulated samples were molded, debindered, and sintered under the above conditions to obtain sintered bodies. Each sintered body sample was evaluated by the above evaluation method. The results are shown in Table 2.

[0040] [Table 2]

[0041] In Examples 1 to 4, sintered bodies with hardness of 250 to 350 Hv and standard deviation of 20 Hv or less were obtained. In these Examples, no cracks or breakage of the processing jig occurred during the subsequent cold plastic processing, and the dimensional variation during the cold plastic processing was within the standard range, and processing up to the center electrode was possible. In Comparative Examples 1, 4, and 5, there were parts with high hardness and large variations. Since parts with hardness exceeding 350 Hv may cause cracks or breakage of the processing jig during the cold plastic processing, subsequent processing was interrupted. In Comparative Examples 2 and 3, there were parts with low hardness and large variations. There were many partial cracks during the subsequent cold plastic processing and large variations in processing dimensions after processing, so processing was interrupted.

[0042] Although some embodiments of the present invention have been illustrated above, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, modifications, etc. can be made without departing from the gist of the invention. Modifications of these embodiments are included in the scope and gist of the invention, and are included in the scope of the invention and its equivalents described in the claims. In addition, the above-mentioned embodiments can be implemented in combination with each other. The invention as originally claimed in the present application is set forth below. [1] A tungsten-based sintered alloy containing 50wt% or more of tungsten with the remainder being Ni, Fe, and Cu, the structure of said tungsten-based sintered alloy having a grain boundary phase mainly composed of Ni, Fe, and Cu and tungsten particles, and the proportion of the length occupied by the grain boundary phase on straight lines crossing opposite sides at right angles in a 270μm×270μm square region in any cut surface of said tungsten-based sintered alloy (linear density) is 0.05 or more and 0.50 or less. [2] The tungsten-based sintered alloy according to [1], wherein the linear density is 0.10 or more and 0.50 or less. [3] The tungsten-based sintered alloy according to [1] or [2], wherein the standard deviation of the linear density is 0.05 or more and 0.10 or less. [4] The tungsten-based sintered alloy according to any one of [1] to [3], wherein the shape of the tungsten particles is such that the outer periphery of the particles is constituted by a boundary that has no acute angles. [5] The tungsten-based sintered alloy according to any one of [1] to [4], characterized in that, for each tungsten particle in a 270μm×270μm square region in any cut surface, the tungsten particle is considered as an ellipse, and the average diameter in two directions is taken as the crystal grain size, the average crystal grain size of the tungsten particle is 20μm or more and 40μm or less. [6] The tungsten-based sintered alloy according to any one of [1] to [5], wherein the measured value of Vickers hardness of an arbitrary cross section is 250 Hv or more and 350 Hv or less, and the standard deviation is 10 to 20 Hv. [7] The method for producing a tungsten-based sintered alloy according to any one of [1] to [6], wherein the raw material powder is granulated by a spray drying method. [8] A discharge electrode member using the tungsten-based sintered alloy according to any one of [1] to [7]. [9] [8] An ignition plug using the discharge electrode member described above. [Explanation of symbols]

[0043] 1. Tungsten-based sintered alloy 2. Tungsten particles 3...grain boundary phase 4...Spark plug 5...Discharge electrode member L1: A straight line that crosses opposite sides at right angles in a square area of ​​270 μm × 270 μm A1~A6: Length across grain boundary phase P … Sintering hole X ... W particle long axis Y ... W particle minor axis Ba: binder aggregates

Claims

1. A tungsten-based sintered alloy consisting of 1.0 wt% or more and 20 wt% or less Ni, 0.1 wt% or more and 10 wt% or less Fe, 0.1 wt% or more and 10 wt% or less Cu, with the remainder being tungsten and unavoidable impurities, wherein the structure of the tungsten-based sintered alloy has grain boundary phases mainly composed of Ni, Fe, and Cu and tungsten particles, and in any cut surface of the tungsten-based sintered alloy, in a 270 μm x 270 μm square region, the proportion of the length occupied by the grain boundary phase on straight lines crossing opposite sides at right angles (linear density) is 0.05 to 0.50, and the standard deviation of the linear density is 0.05 to 0.

10.

2. 2. The tungsten-based sintered alloy according to claim 1, wherein the linear density of the tungsten-based sintered alloy is 0.10 or more and 0.50 or less.

3. 3. The tungsten-based sintered alloy according to claim 1, wherein the tungsten particles have a shape in which the outer periphery is formed of a boundary having no acute angles.

4. The tungsten-based sintered alloy according to any one of claims 1 to 3, characterized in that, in the tungsten-based sintered alloy, for each tungsten particle in the 270μm×270μm square region in any cut surface, tungsten particle is regarded as an ellipse, and the value obtained by (Y+X) / 2 using the orthogonal major axis (X) and minor axis (Y) of the tungsten particle is the crystal grain size, the average crystal grain size of tungsten particle is 20μm or more and 40μm or less.

5. The tungsten-based sintered alloy according to any one of claims 1 to 4, wherein the Vickers hardness of any cross section is 250Hv or more and 350Hv or less, and the standard deviation is 10 to 20Hv.

6. 6. The method for producing a tungsten-based sintered alloy according to claim 1, wherein the raw material powder is granulated by a spray drying method.

7. A discharge electrode member using the tungsten-based sintered alloy according to any one of claims 1 to 5.

8. 8. A spark plug comprising the discharge electrode member according to claim 7.

Citation Information

Patent Citations

  • Sealing method for pump

    JP1983047196A

  • Heat dissipating structural member made of tungsten-base sintered alloy for semiconductor device

    JP1993326765A

  • Slider material made of w-based sintered alloy for current collector of high-speed electric vehicle

    JP1994279909A

  • High density material, and production method therefor

    JP2004149813A

  • Weight made of tungsten-based sintered alloy

    JP2004353006A